Visible-Light-Induced Methylation of Quinoxalin-2(1H)-ones Catalyzed by Dye Molecules - Wei, Lin-Lin; Chen, Qi; Wang, Jing-Yun; Sun, Jing; Chen, Yang; Zhou, Ming-Dong (Synthesis, 2025)
A visible-light-driven, molecular dye-catalyzed C-3 methylation strategy for quinoxalin-2(1H)-ones has been successfully developed. The methodology demonstrates broad substrate compatibility with various substituted quinoxalin-2(1H)-ones, which could react with N,N,N′,N′,N′′-pentamethyldiethylenetriamine (PMDETA) efficiently at room temperature under ambient atmospheric conditions to afford the corresponding 3-methylquinoxalinone derivatives in moderate to good yields. It is noteworthy that this protocol offers a simple, clean, and transition-metal-free approach, establishing a practical and eco-friendly methodology for constructing diverse C3-methylated quinoxalinone scaffolds, complementing existing synthetic strategies for site-selective functionalization of these heterocycles.
Keywords: photocatalysis; methylation; quinoxalin-2(1H)-ones; dye molecules; photosensitizers